2013
DOI: 10.1016/j.celrep.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia Cells Are Activated and Proliferate in Response to Specific T Helper Cells

Abstract: There is increasing interest in the chronic lymphocytic leukemia (CLL) microenvironment and the mechanisms that may promote CLL cell survival and proliferation. A role for T helper (Th) cells has been suggested, but current evidence is only circumstantial. Here we show that CLL patients had memory Th cells that were specific for endogenous CLL antigens. These Th cells activated autologous CLL cell proliferation in vitro and in human → mouse xenograft experiments. Moreover, CLL cells were efficient antigen-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 47 publications
6
107
1
Order By: Relevance
“…Very recently, we found that CLL patients had Th1-like cells that responded to endogenous CLL cell Ag presented by CLL cells on HLA class II molecules (11). Such Th cells supported the activation and expansion of CLL cells in vitro and in xenografted mice.…”
Section: Hronic Lymphocytic Leukemia (Cll) Is a Malignancy Of Expanmentioning
confidence: 79%
See 3 more Smart Citations
“…Very recently, we found that CLL patients had Th1-like cells that responded to endogenous CLL cell Ag presented by CLL cells on HLA class II molecules (11). Such Th cells supported the activation and expansion of CLL cells in vitro and in xenografted mice.…”
Section: Hronic Lymphocytic Leukemia (Cll) Is a Malignancy Of Expanmentioning
confidence: 79%
“…The transcription factor T-bet is the key regulator in Th1 cell polarization and type 1 immune responses (15) and has also been detected in CLL cells (11,16). In murine B cells, T-bet plays a role in B cell migration (17) and is essential for class switch to IgG2a and for IFN-g production (15,18,19).…”
Section: Hronic Lymphocytic Leukemia (Cll) Is a Malignancy Of Expanmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Several studies suggest that CLL cells are rescued by combined BCR and CD40L triggering; an anti-apoptosis, activation and differentiation signal is mediated by T helper (Th) cells via CD40L (CD40 ligand, CD154) that binds CD40 on the B cell surface. [6][7][8][9][10] Thus, CLL patients have CLL-specific Th cells that can support CLL cell proliferation in xenografts, 8,9 activated CD40L + Th cells colocalize with proliferating CLL cells in pseudofollicles, 6,7 and CLL cells secrete Th attracting chemokines, thereby recruiting T cell help. 6,9 It has been unclear how BCR pathway inhibitors impact the microenvironmental help of CLL cells.…”
mentioning
confidence: 99%